PENGARUH TOTAL QUALITY MANAGEMENT DAN QUALITY MANAGEMENT INFORMATION TERHADAP KINERJA PERUSAHAAN - OEY HANNES WIDJAYA; IAN NURPATRIA SURYAWAN (Media Bisnis, 2014)
This study aimed to determine the effect of total quality management and quality management information on the firm performance which Is a company engaged in tire manufacturing. A method of data collection is done by distributing questionnaires to all employees’ quality assurance totaling 19 people. The test results suggest that there is a positive influence of total quality management and quality management information on the firm performance.